The Use of Animated Videos in Teaching Prophetic Stories to Early Childhood Students at Taska Aspirasi Intelek, Shah Alam, Malaysia - Dewi, Nurliza; Pasaribu, Munawir (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The teaching of Prophet stories plays a significant role in establishing the foundation of religious values in early childhood. By employing creative approaches, such as animated videos, the learning process becomes more engaging and effective. The aim of this study is to analyze the extent to which animated videos can enhance students' understanding and interest in learning about the stories of Prophets. The research was conducted at Taska Aspirasi Intelek, Shah Alam, Malaysia, using a qualitative approach with a descriptive method. Data collection techniques included direct observation, interviews with educators, and document analysis related to the use of video media in learning activities. The findings reveal that the use of animated videos captures students' attention and facilitates the delivery of Prophet stories in an interactive and enjoyable way. Animated videos provide visualizations that enhance children's memory retention, making it easier for them to recall storylines and the moral messages conveyed. However, active guidance from educators remains essential to optimize the learning process and assist students in comprehending the messages embedded in the stories.